2015
DOI: 10.1007/978-3-319-19060-0_10
|View full text |Cite
|
Sign up to set email alerts
|

Water at Biological Phase Boundaries: Its Role in Interfacial Activation of Enzymes and Metabolic Pathways

Abstract: Many life-sustaining activities in living cells occur at the membrane-water interface. The pertinent questions that we need to ask are, what are the evolutionary reasons in biology for choosing the membrane-water interface as the site for performing and/or controlling crucial biological reactions, and what is the key physical principle that is very singular to the membrane-water interface that biology exploits for regulating metabolic processes in cells? In this chapter, a hypothesis is developed, which espous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…At present the proposed mechanism involves selective absorption of IR photons by structured water layers (also known as interfacial water) [26] or water clusters [27], at power levels that are insufficient to cause any detectable bulk-heating of the tissue. A small increase in vibrational energy by a water cluster formed in or on a sensitive protein such as a heat-gated ion channel, could be sufficient to perturb the tertiary protein structure thus opening the channel and allowing modulation of intracellular calcium levels [28]. Pollack has shown that interfacial water can undergo charge separation when it absorbs visible or NIR light [29].…”
Section: Chromophores Responsible For Photobiomodulationmentioning
confidence: 99%
“…At present the proposed mechanism involves selective absorption of IR photons by structured water layers (also known as interfacial water) [26] or water clusters [27], at power levels that are insufficient to cause any detectable bulk-heating of the tissue. A small increase in vibrational energy by a water cluster formed in or on a sensitive protein such as a heat-gated ion channel, could be sufficient to perturb the tertiary protein structure thus opening the channel and allowing modulation of intracellular calcium levels [28]. Pollack has shown that interfacial water can undergo charge separation when it absorbs visible or NIR light [29].…”
Section: Chromophores Responsible For Photobiomodulationmentioning
confidence: 99%
“…To cover the high demand of synthesis involving hydrophobic substrates and/or products, biocatalysis in unconventional media (i.e., organic solvents) is a powerful technique leading to high yields [1][2][3]. However, biocatalysts require a minimum water activity in the media to achieve an adequate catalytic activity [4][5][6]. To provide this, two-phase systems in which the biocatalyst is located in the aqueous phase, guaranteeing its activity, and the hydrophobic reactants predominate in the organic phase are promising alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…The membrane interface (see Figure a) ensures a dynamic segregation of the bulk (outer) aqueous phase from the more isotropic, hydrophobic membrane core and exhibits distinct chemical, motional, and dielectric signatures . This region, owing to its unique physicochemical properties, plays a crucial role in modulating biochemical processes such as substrate recognition and function of membrane-active enzymes. At a molecular level, the membrane interface imposes a dynamic spatiotemporal confinement on water molecules due to reduced probability of energetically favorable hydrogen bonding induced by geometrical constraints . As a result, the membrane interface displays slow rates of solvent relaxation and is involved in intermolecular charge interactions and hydrogen bonding mediated by polar phospholipid headgroups. , …”
Section: Introductionmentioning
confidence: 99%